Origin of Synthetic Particles in Honeys - Liebezeit Gerd; Liebezeit Elisabeth (Polish Journal of Food and Nutrition Sciences)
A total of 47 honeys and 22 flowering plants was analysed for their load of synthetic fibres and fragments. In all samples investigated foreign particles were found. These include also black carbon particles which were not enumerated. Fibres and fragments ranged from 10 to 336 kg-1 and 2 to 82 kg-1 honey, respectively. The data of the flowering plants analysed indicate that a major proportion of the particle load may originate from external sources, i.e. these particles are brought into the beehive by the worker bees during nectar collection.